PENGARUH MODEL PEMBELAJARAN KOOPERATIF BERBANTUAN SCRAMBLE TERHADAP HASIL BELAJAR TEMA 1 ALAT GERAK HEWAN DAN MANUSIA KELAS V GUGUS 5 KECAMATAN SELAPARANG TAHUN AJARAN 2019/2020 - Amnah Aulia Miranty; Ahmad Harjono; Abdul Kadir Jaelani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
This study aims to determine the effect of cooperative learning models assisted scramble toward theme 1 animal and human motion tools study result of 5thgrade at 5th selaparang sub-district school year 2019/2020. This research is experimental research with a type of quasi-experimental and the design is nonequivalent control group design. The data is collected through observation and tests. The data were analyzed with a normality test, homogeneity test and hypothesis test using an independent sample t-test. The analysis showed that the significant level of test = 0.00 was less than 0.05 (0.00 <0.05). Based on testing criteria, if the t-test <0.05, Ha is accepted and H0 is rejected. This means that cooperative learning models assisted scramble influential toward theme 1 animal and human motion tools study result of 5th grade at 5th selaparang sub-district school year 2019/2020.